2022
DOI: 10.1055/a-1978-3277
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete resection of colorectal polyps of 4–20 mm in size when using a cold snare, and its associated factors

Abstract: Background: Cold snare polypectomy (CSP) is increasingly used for polypectomy and is recommended as first-line modality for small (<10mm) polyps. This study aimed to evaluate incomplete resection rates (IRRs) when using CSP for 4-20mm colorectal polyps. Methods: Adults (45-80y) undergoing screening, surveillance, or diagnostic colonoscopy were included to undergo CSP by nine endoscopists. Primary outcome was IRR for 4-20mm colorectal polyps, defined as presence of polyp tissue in marginal biopsies after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Complete resection of colorectal polyps is of obvious importance. It has been estimated that 20 % of post-colonoscopy cancers may be caused by incompletely removed polyps [3].In this issue of Endoscopy, von Renteln et al offer another piece of the puzzle regarding the usefulness of the CSP technique [4]. In their single-center prospective cross-sectional study, the authors investigated the IRR of 128 colorectal polyps sized 4-20 mm.…”
mentioning
confidence: 99%
“…Complete resection of colorectal polyps is of obvious importance. It has been estimated that 20 % of post-colonoscopy cancers may be caused by incompletely removed polyps [3].In this issue of Endoscopy, von Renteln et al offer another piece of the puzzle regarding the usefulness of the CSP technique [4]. In their single-center prospective cross-sectional study, the authors investigated the IRR of 128 colorectal polyps sized 4-20 mm.…”
mentioning
confidence: 99%
“…For polyps of 4–10 mm, CSP was recommended as it induce less injury to the submucosal arteries than polypectomy methods using electrocautery ( 19 ). However, The incomplete resection rate can reach 18.4% in a recent study using CSP, ( 20 ) which is worse than a previous study (CARE study) with comparable design using HSP ( 11 ). Evidence comparing efficacy with HSP is lacking.…”
Section: Introductionmentioning
confidence: 61%
“…A previous study conducted by our research group showed that CSP without SI for 4-to 20-mm colorectal polyps resulted in high IRR (24/128 = 19 %) (12.4 %-26.6 %) [15]. We considered a reduction to 8.5 % to these previous findings as clinically significant for demonstrating clinical superiority of CSP-SI.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 89%
“…A recent meta-analysis indicated that incomplete resection rates (IRRs) when using CSP is high but comparable to IRRs when using hot snare polypectomy (HSP) [14]. A previous study conducted by our research group showed that CSP without SI for 4-to 20-mm colorectal polyps resulted in 19 % IRR [15]. In contrast, another study showed that wide-field cold polypectomy with SI was associated with a much lower IRR (1.2 %) when used for resection of large (> 10 mm) serrated lesions (SLs) [16].…”
Section: Introductionmentioning
confidence: 90%